COVID-19 and the militarization of the State in Brazil - Rodrigues, Thiago; Fedatto, Maira [UNESP]; Kalil, Mariana (Univ Complutense Madrid, Servicio Publicaciones, 2021)
Brazil has been hit hard by the new coronavirus pandemic. In such a context, there has been an increasing transference of decision-making and policy-making power to the military, and the Brazilian national response to COVID-19 has eventually come under military authority. Based on the current debate on the on-going securitization of public health in the world following the outbreak of the new coronavirus, we engage with recent literature in an attempt to demonstrate Brazil's singular pattern of military interference in public health. It is our hypothesis that in Brazil there is a process of militarization of the responses to the pandemic without, however, a concomitant process of securitization. This is possible because the Bolsonaro Administration combines denialism toward the COVID-19 pandemic with the gradual delegation of key political roles to the military. We claim, finally, that the Brazilian case of military response to COVID-19 offers analytical instruments to study other cases of imbalance in civil-military relations throughout the Global South.
Keywords: Brazil; Latin America; Militarization; Securitization; COVID-19; Civil-military relations